MANAGEMENT OF INNOVATION ACTIVITIES IN WAR CONDITIONS - ВABCHYNSKA Olena; POSVALIUK, Olha; SKAKUN, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes innovative development in Ukraine as an important component of transformation processes in the context of significant losses and serious difficulties. The focus is on the importance of state support for domestic high-tech industries and innovation initiatives. It is also important to create favorable conditions for small and medium-sized businesses and develop investment mechanisms that combine public and private capital to finance innovations, and measures are provided to support innovation and investment activities by the state. The current conditions for conducting economic activity in Ukraine are largely determined by the challenges associated with a full-scale war. The armed conflict has caused significant economic, social and technological changes that have significantly affected the functioning of enterprises, in particular the ability to initiate, support and scale innovation processes. Innovation activity, which is the driver of economic development and increased competitiveness, acquires particular relevance in conditions of martial law. On the one hand, war limits resources, disrupts logistics chains, reduces investment attractiveness and creates threats to the implementation of long-term projects. On the other hand, force majeure circumstances stimulate the search for non-standard solutions, acceleration of digital transformation, development of defense and critical technologies, adaptation of organizations to new conditions through flexible innovation management. Management of innovation activity in conditions of war requires new approaches to strategic planning, resource provision, risk management and organizational flexibility. There is a need to revise traditional management models in favor of more adaptive and crisis-resistant ones that can ensure the stability and development of enterprises even in emergency conditions.